2017
DOI: 10.1016/j.jip.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Spatial relationships between entomopathogenic nematodes and nematophagous fungi in Florida citrus orchards

Abstract: Relationships between entomopathogenic nematodes (EPNs), nematophagous fungi (NF) and soil physical and chemical properties were studied in a survey of 53 citrus orchards in central ridge and flatwoods ecoregions of Florida. Seven species of NF associated with nematodes were quantified directly using a real time qPCR assay. All nematophagous fungi studied except Arthrobotrys musiformis and Hirsutella rhossiliensis were frequently detected (24-56%) in both regions. Paecilomyces lilacinus and Gamsylella gephyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…This is timely with the frequently reported incidence of naturally occurring communities of nematophagous fungi and parasitic bacteria such as Pasteuria species in citrus orchards (Shokoohi and Duncan 2018). Pathak et al (2017) demonstrated habitat variation in the predominance of two of seven species of biocontrol fungi found in the DNA recovered from samples of nematodes in citrus orchards. The predator-prey model parameters for a Pasteuria sp.…”
Section: Nematicidal Applicationsupporting
confidence: 67%
“…This is timely with the frequently reported incidence of naturally occurring communities of nematophagous fungi and parasitic bacteria such as Pasteuria species in citrus orchards (Shokoohi and Duncan 2018). Pathak et al (2017) demonstrated habitat variation in the predominance of two of seven species of biocontrol fungi found in the DNA recovered from samples of nematodes in citrus orchards. The predator-prey model parameters for a Pasteuria sp.…”
Section: Nematicidal Applicationsupporting
confidence: 67%
“…It is likely that not only abundance but also the proportions of the identified NF species could be one of the keys to explaining these observations. We reported significantly higher presence of NF-IR on grassseeded covers, the treatment that recorded the highest content in organic matter and the lowest sand percentages, two of the key factors that favor NF occurrence on soils (Nordbring-Hertz et al, 2006;Pathak et al, 2017). Endoparasitic fungi (H. rhossilliensis and Catenaria sp.)…”
Section: Discussionmentioning
confidence: 82%
“…Recent greenhouse trials also showed that parasitism of H. rhossiliensis was strongly correlated with the density of the soybean cyst nematode [30]. At broader geographic scales, in a survey of 53 citrus orchards in central ridge and flatwood ecoregions of Florida, the spatial patterns of entomopathogenic nematode species were found to be modulated by variations in their susceptibilities to nematophagous fungal species (Catenaria sp., A. musiformis, Arthrobotrys dactyloides, Paecilomyces lilacinus, A. oligospora, and Gamsylella gephyropaga) across habitats [95]. However, strong and diverse top-down control effects on the nematode community in coastal sand dunes were found in a recent study, where three microbial enemies of nematodes (Catenaria spp., H. rhossiliensis, and Pasteuria penetrans) were correlated, either positively or negatively, with plant parasitic nematode population size [96].…”
Section: Competition Between Different Fungal Species and Nematodesmentioning
confidence: 95%